2015
DOI: 10.1128/jcm.02595-14
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Immunochromatographic Assay Kit Using Fluorescent Silica Nanoparticles for Rapid Diagnosis of Acanthamoeba Keratitis

Abstract: We developed an immunochromatographic assay kit that uses fluorescent silica nanoparticles bound to anti-Acanthamoeba antibodies (fluorescent immunochromatographic assay [FICGA]) and evaluated its efficacy for the detection of Acanthamoeba and diagnosis of Acanthamoeba keratitis (AK). The sensitivity of the FICGA kit was evaluated using samples of Acanthamoeba trophozoites and cysts diluted to various concentrations. A conventional immunochromatographic assay kit with latex labels (LICGA) was also evaluated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
0
13
0
2
Order By: Relevance
“…However, their application efficacy for OPPP monitoring in premise plumbing is still subject to the concentration level of target cells and availability of high quality antibodies. It has been reported that selected antibodies might not be able to cover the whole range of serogroups or species (Keserue et al, 2012) and validation of specificity and sensitivity against environmental background is often lacking (Toriyama et al, 2015; Visvesvara et al, 1987). …”
Section: Detection Methodsmentioning
confidence: 99%
“…However, their application efficacy for OPPP monitoring in premise plumbing is still subject to the concentration level of target cells and availability of high quality antibodies. It has been reported that selected antibodies might not be able to cover the whole range of serogroups or species (Keserue et al, 2012) and validation of specificity and sensitivity against environmental background is often lacking (Toriyama et al, 2015; Visvesvara et al, 1987). …”
Section: Detection Methodsmentioning
confidence: 99%
“…An aggregation-based assay was demonstrated by Jayawardana and co-workers (2015) for the detection of the model bacteria Mycobacterium smegmatis. Japanese company Furukawa Electric has used commercialised a lateral flow assay incorporating fluorescent silica NPs, called Quartz Dots (290 nm) for the detection of different infectious microorganisms (Toriyama et al 2015).…”
Section: Immunoassays and Biosensorsmentioning
confidence: 99%
“…5(e)). 78 Silica nanoparticles doped with cyanine-5 (Cy5), the most commonly used fluorescent dye in biological assays, has been reported for use in the development of fluorescence-based lateral flow immunoassay (LFIA) for influenza A antigen detection. Carboxyl-modified silica nanoparticles (50 nm), prepared by Stober method, were linked to the amino group of monoclonal antibody specific to influenza A nucleoprotein through carbodiimide chemistry.…”
Section: •2•2 Silica Nanoparticle As a Tracing Tag To Label Signalmentioning
confidence: 99%